THE RELATIONSHIP OF HOPE WITH QUARTER LIFE CRISIS IN FINAL YEAR STUDENTS IN WEST SUMATRA - dinda aisyah; Rinaldi (Causalita, 2024)
This research aims to determine the relationship between hope and quarter life crisis in final year students in West Sumatra. Hope is the ability possessed by an individual to create a strategy in achieving a goal with the overall motivation he has to recognize the strategy chosen in achieving a goal. Meanwhile, the quarter life crisis is a process of high instability, drastic changes, too many choices and feelings of panic and helplessness. This phase appears in individuals aged 18 to 29 years. This research uses quantitative methods with a quantitative correlational research design. The population in this study were final year students in West Sumatra with a total of 195 students as subjects. The sampling technique used was purposive sampling. The data collection tool uses the quarter life hope and crisis scale. Data analysis uses the product moment correlation coefficient. The results of the research show that there is a negative relationship between hope and the quarter life crisis in final year students in West Sumatra (r=-0.514: p=0.00). A significant negative relationship means that if an individual has high hopes then the level of quarter life crisis for the individual will be low, and if the level of quarter life crisis is high then the level of hope experienced by the individual will tend to be low.